Liderazgo resonante en las pymes panificadoras de la ciudad de Barranquilla (2020)
The research describes the resounding leadership in the bakery SMEs in the city of Barranquilla. According to a quantitative methodology, of descriptive type, field design, transversal, and nonexperimental, using as observation units seven hundred and sixty-nine (769) subjects belonging to the bakery sector located in the city of Barranquilla. The survey technique was used and as an instrument a questionnaire structured by thirty (30) items, validated by the judgment of ten (10) experts, with a reliability of (0.81) according to the Cronbach Alpha coefficient, being highly reliable, For the analysis of the data, the coding and tabulation was performed, with Microsoft Excel (.xlsx). The findings show the presence of resonant leadership in the bakery SMEs in the city of Barranquilla, with the resonant leadership styles dimension being the most favored, followed by resonant leadership according to gender, and with a lower appreciation of the current situation. It is concluded, how vital it is to possess and develop resonant leadership styles, which adapt to the needs of the company and its environment, respecting gender equality, and valuing the current situation day after day, in order to design strategies for the management of human talent, that respond to market demands, without neglecting internal and external factors of the company, under the principle of social responsibility, innovation and adaptation to changes.